Low-Cost Smartphone-Operated Readout System for Point-of-Care Electrochemical and Photoelectrochemical Biosensing - Scott, Alexander (My University, 2021)
Despite the increasing number of electrochemical and photoelectrochemical biosensors reported in the research literature, few have achieved success outside of a laboratory setting. This can partly be attributed to accessibility issues with commercially available readout instruments. Consequently, low-cost and portable readout instruments have been developed by researchers, but these devices fail to address other key compatibility and accessibility challenges. Much like the commercial systems, these devices are not natively compatible with multiplexed signal assays consisting of two or more working electrodes, cannot control optical excitation sources for photoelectrochemical biosensing, nor can they interface with auxiliary instruments such as heaters and electromagnets. To this end, we have developed a low-cost smartphone-operated electrochemical and photoelectrochemical readout system for point-of-care biosensing. Our readout system can perform standard voltammetric techniques and is capable of synchronously controlling an optical excitation source to support photoelectrochemical biosensing. This device is compatible with standard three-electrode assays as well as dual signal assays with two working electrodes. We have also created a portable sample heater that can be controlled by this readout system to facilitate on-site sample heating and have also integrated a portable electromagnet to perform away-from-lab magnetic manipulation.
Keywords: potentiostat; point-of-care; photoelectrochemistry; electrochemistry; biosensing; readout; readout instrument; smartphone-operated; actuation; DNA detection; voltammetry; multiplex; DNAzyme; Android